Literature Review The Relationship Of Antenatal Class Towards Mothers’ Knowledge Of DangerousSign During Pregnancy - Ayu Kurniati; Enny Fitriahadi; Fuad Gandhi Torizal (International Journal of Health Science and Technology, 2021)
IN 2013, the World Health Organization, released data in the form of Maternal Mortality Rate (MMR) worldwide, and the number reached 289,000 per 100, 000 live births, which 99% of cases occurred in developing countries. Research aims to discover the relationship of antenatal class towards mothers’ knowledge of the dangerous sign during pregnancy. The result showed that there is a relationship of antenatal class towards mothers’ knowledge of dangerous sign during pregnancy, From this result, the researcher concludes that antenatal class could increase mothers’ knowledge of dangerous sign during pregnancy and may decrease the complication risk during the childbirth.